2002
DOI: 10.1128/aac.46.4.1114-1116.2002
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities of Mycobacterium marinum to Gatifloxacin, Gemifloxacin, Levofloxacin, Linezolid, Moxifloxacin, Telithromycin, and Quinupristin-Dalfopristin (Synercid) Compared to Its Susceptibilities to Reference Macrolides and Quinolones

Abstract: The susceptibility pattern of Mycobacterium marinum was determined. Quinupristin-dalfopristin and telithromycin were less active than clarithromycin. Linezolid showed good antimicrobial activity at clinically achievable concentrations. Gatifloxacin, levofloxacin, and moxifloxacin displayed activities similar to those of ciprofloxacin. Gemifloxacin was less active. The Etest method showed variable agreement with the reference method.Mycobacterium marinum was recognized as a human pathogen in 1959 (13). Infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…From then on, several studies, based on different methods such as agar dilution, radiometric respirometric technique (Bactec) and stable gradient test (Etest), confirmed the first observations [4,5,6,7,8,9,10,11,12,13]. …”
Section: Discussionmentioning
confidence: 49%
“…From then on, several studies, based on different methods such as agar dilution, radiometric respirometric technique (Bactec) and stable gradient test (Etest), confirmed the first observations [4,5,6,7,8,9,10,11,12,13]. …”
Section: Discussionmentioning
confidence: 49%
“…- [89,90]; HAE: M. haemophilum [2]; a lack of consistency in susceptibility results [2]. b see [32] for further discussion; c in [89] discussed as resistant Table 4 In vitro susceptibility of selected NTM to various antimycobacterial agents.…”
Section: Antibiotic [Reference] Mac Kan Abs For Che Mal a Xen A Mar Haementioning
confidence: 99%
“…Most isolates described in the literature are susceptible to amikacin or tobramycin, one of the fluoroquinolones, and to clarithromycin. 30,33,56,71,74 A combination of these drugs as the initial topical treatment of suspected cases until culture and susceptibility tests are available may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…41,[47][48][49][50][51][52] Although in vitro activity does not always accurately predict therapeutic efficacy, in vitro tests may aid in determining the best antibiotic coverage, particularly when MIC results are available. 53 Some in vitro studies have shown that amikacin, ciprofloxacin, norfloxacin, vancomycin, tobramycin, and gentamicin can be active against rapidly growing mycobacteria (RGM), [32][33][34][54][55][56] but there are few drugs that are active against M. chelonae and M. abscessus. 28,52,[57][58][59] In vitro susceptibility tests with the newer fluoroquinolones (8-methoxy fluoroquinolones), gatifloxacin and moxifloxacin, have shown that gatifloxacin is more active than ciprofloxacin against various mycobacterial species.…”
mentioning
confidence: 99%